Angiokeratomas, not everything is Fabry disease. (17th January 2019) - Cuestas, Daniel; Perafan, Alejandra; Forero, Yency; Bonilla, Juan; Velandia, Alexander; Gutierrez, Ana; Motta, Adriana; Herrera, Hugo; Rolon, Mariam
Abstract: Introduction: Angiokeratoma corporis diffusum are benign capillary malformations typically associated with Fabry disease and other lysosomal storage disorders. Only in a few cases they appear in healthy individuals. Methods and Case: We carried out an exhaustive review of the literature on angiokeratomas and their main clinical, dermoscopy and histological features. Additionally, we reviewed the cases of healthy subjects illustrating the limitations of each case and comparing these results with our case. Discussion: Angiokeratoma corporis diffusum is mostly related to Fabry disease and other lysosomal storage disorders. However, some cases may occur in apparently healthy individuals. Therefore, there is a increasing interest in its etiology, pathogenesis and clinical evaluation. Conclusion: This is an academic–clinical review on angiokeratomas and their main implications in daily dermatological practice. Additionally, we report the first case in the literature of angiokeratoma corporis diffusum in a healthy patient with up‐to‐date laboratory methods currently available. The clinician should remember that not all angiokeratoma corporis diffusum occurs with lysosomal storage disorders.